well dear speed
f(x) = 1-x^2
f(1-a) = ?
x = 1-a , means any where u see 'x' just fill it with '1-a'
f(1-a) = 1-(1-a)^2
{ (a-b)^2 = a^2 + 2ab +b^2 }
f(1-a) =1 - [(1^2) - (2*1*a) + ( a^2)]
f(1-a) =1- ( 1 -2a +a^2)
f(1-a) =1- 1 +2a -a^2
f(1-a) = 2a-a^2
Good Luck.
2006-09-23 10:29:16
·
answer #1
·
answered by sweetie 5
·
1⤊
0⤋
Substitute 1-a for x in the definition of f(x)
f(1-a) = 1-(1-a)² = 1 - (1 - 2a + a²) = 2a - a²
Doug
2006-09-23 10:16:13
·
answer #2
·
answered by doug_donaghue 7
·
0⤊
0⤋
I will solve it more scientifically,
Refer back to some equation rules:
Let use a^2 - b^2 = (a+b)(a-b),
f(x) = 1 - x^2
f(1-a) = 1 - (1-a)^2
f(1-a) = [1+(1-a)][1-(1-a)]
= (1+1-a)(1-1+a)
= (2-a)(a) OR
= 2a -a^2
I hope you are expecting this way of answering your question
2006-09-23 10:24:32
·
answer #3
·
answered by davidkwankwokfai 3
·
0⤊
0⤋
f(1 - a) = 1 - (1 - a)^2
f(1 - a) = 1 - ((1 - a)(1 - a))
f(1 - a) = 1 - (1 - a - a + a^2)
f(1 - a) = 1 - (1 - 2a + a^2)
f(1 - a) = 1 - 1 + 2a - a^2
f(1 - a) = -a^2 + 2a
2006-09-23 14:42:20
·
answer #4
·
answered by Sherman81 6
·
0⤊
0⤋
Substitute:
f(1-a)=1-(1-a)²
Expand:
f(1-a)=1-(1-2a+a²)
Distribute:
f(1-a)=1-1+2a-a²
Cancel:
f(1-a)=2a-a²
Thus your solution is f(1-a)=2a-a² .
2006-09-23 10:16:04
·
answer #5
·
answered by Pascal 7
·
1⤊
2⤋
f(1-a) = 1-(1-a)^2
simplify
2006-09-23 10:25:49
·
answer #6
·
answered by Helmut 7
·
0⤊
2⤋